Ensouling the Beatific Vision. Motivating the Reformed Impulse - Farris, Joshua R. (Perichoresis, 2017)
The beatific vision is a subject of considerable importance both in the Christian Scriptures and in the history of Christian dogmatics. In it, humans experience and see the perfect immaterial God, which represents the final end for the saints. However, this doctrine has received less attention in the contemporary theological literature, arguably, due in part to the growing trend toward materialism and the sole emphasis on bodily resurrection in Reformed eschatology. As a piece of retrieval by drawing from the Scriptures, Medieval Christianity, and Reformed Christianity, we motivate a case for the Reformed emphasis on the immaterial and intellectual aspects of human personal eschatology and offer some constructive thoughts on how to link it to the contemporary emphasis of the body. We draw a link between the soul and the body in the vision with the help of Christology as reflected in the theology of John Calvin, and, to a greater extent, the theology of both John Owen and Jonathan Edwards.